Optimization of Cooking Time of Chicken Meat Loaf Prepared With Oven Cooking - Singh, Sanjay; Pathak, Vikas; Goswami, Meena; Verma, Arun Kumar; V, Rajkumar; Kumari, Renu (Journal of Meat Science, 2022)
The present study was carried out to effect of oven cooking at 180ºC for 15 minutes (OC1), 20 minutes (OC2) and 25 minutes (OC3) on various physico-chemical properties, texture profile analysis, colour parameter, mineral content as well as sensorial properties of chicken meat loaf. There was no significant difference in pH, protein and ash content among the treatments. Cooking yield, moisture content, fat retention, water activity and moisture retention values decreased significantly (P<0.05); however fat, carbohydrate and cholesterol content increased significantly (P<0.05) with increased time of cooking. The values of all textural parameters except gumminess and resilience increased significantly (P<0.05) with increased time of cooking. Lightness and yellowness values decreased significantly (P<0.05); however redness value increased significantly (P<0.05) with increased time of cooking. There was no significant difference in zinc, chromium and magnesium content among the treatments. Potassium, sodium, calcium, copper, manganese, iron and phosphorous content increased significantly (P<0.05) with increased time of cooking; however no significant difference was observed in copper content between OC1 and OC2. OC2 had significantly (P<0.05) higher sensory scores except saltiness and mouth coating scores. Therefore, it was concluded that well acceptable chicken meat loaf could be prepared by oven cooking 180ºC for 20 minutes.